Inventarisasi Kebijakan Publik (Kajian di Desa Buluh Cina Kecamatan Siak Hulu Kabupaten Kampar) - Muhammad Ridwan; Khairul Anwar; Auradian Marta (Nakhoda: Jurnal Ilmu Pemerintahan, 2011)
This research purpose to analize roles and relation form between Village Head and BadanPermusyawaratan Desa (BPD) Buluh Cina Village on making decision expecially Village regulation. Thisresearch is case sudy with qualitative method. The data in this research collected with observation, depthinterview and documentation study. Based the research show that Village head and BadanPermusyawaratan Desa (BPD) have a role in active on making Village regulation. Partnership betweenVillage head and Badan Permusyawaratan Desa (BPD) on making Village regulation indicatedharmonisasi village government institutionalism.